Lyme disease: Modern approaches to prevention, diagnosis and treatment - B. S. Belov; L. P. Ananyeva (Научно-практическая ревматология)
Lyme disease (LD) or tick-borne borreliosis affects thousands of people every year in different regions of the world, primarily the United States and Europe. In endemic areas, early LD is a common disease that requires high medical vigilance. Considering the extreme relevance of this problem for public health, in November 2020, the committee of experts of three American scientific societies published an updated version of the clinical guidelines for the prevention, diagnosis and treatment of LD, the main provisions of which are presented in this article. It is emphasized that in the absence of vaccines, the risk of LD and other diseases transmitted by ticks can be reduced by using personal protective equipment and repellents. Antibiotic prophylaxis is carried out by a single oral administration of doxycycline. In the laboratory diagnosis of LD, the determination of antibodies to B. burgdorfery in the blood serum is a first-line study. At the second stage, serum samples are examined using an immunoblot for IgM and IgG. The basis of treatment of LD is rational antibiotic therapy. The choice of an antibiotic depends on a number of factors, including the presence of extracutaneous manifestations of LD (neuroborreliosis, carditis, arthritis). The most commonly used are doxycycline, amoxicillin, cefuroxime-axetil and ceftriaxone.